EFEKTIVITAS METODE PICTURE AND PICTURE DALAM MENINGKATKAN KEMAMPUAN KOSAKATA BAHASA JEPANG PADA SISWA KELAS X SMA N PINTAR TELUK KUANTAN - Sisma Sri Kurniawati; Hadriana Hadriana; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research discusses about Picture and Picture method on Japanese Vocabulary Lesson for the class X Students of Pintar Senior High School in TalukKuantan. The aim of this research is to know the significant difference between the study result of students who used picture and picture as learning method for Japanese Vocabulary and students who did not. The object of this research was the Class X Students of Pintar Senior High School in TalukKuantan. There are two class that used as object of this research i.e XA and XB. This research is a quasy experimental research with pretest posttest design.This design was conducted in two class, with XA as control class and XB as experimental class. The type of data collection technique in this research is giving a test.The test consisted of two types, namely pretest and posttest.These tests were conducted to compare the students’ Japanese vocabulary skills before and after being given treatment.Based on the result of Independent Sample t test, it was found that the significance value (sig) (2-tailed) was 0,000 < 0.005. It means that there is a significant difference between the study result of students who used picture and picture as learning method for Japanese Vocabulary and students who did not. In other word, Picture and Picture method is effective to improve Japanese vocabulary skill of class X students in Pintar Senior High School TalukKuantanKey Words: Vocabulary, Picture and Picture Method, Cooperative Learning